Nest-site selection and breeding biology of the locally endangered Micronesian Starling (Aplonis opaca) informs its recovery on Guam - Julie A. Savidge; Martin Kastner; Henry S. Pollock; Thomas F. Seibert (Avian Conservation and Ecology, 2022)
Micronesian Starlings (Aplonis opaca) are one of two native forest bird species that have survived on the island of Guam despite predation by invasive brown tree snakes (Boiga irregularis). We report the first detailed account of the starling’s breeding biology to help understand how this species has persisted and guide management to conserve and expand the population. Our surveys indicated that although starlings continued to forage in nearby forest, nesting occurred almost exclusively in developed habitat on Andersen Air Force Base. We located 36 active nest sites in a variety of natural and artificial structures, many of which were likely difficult or impossible for snakes to access. We report reproductive data from those nest sites and also predator-resistant nestboxes (n = 48 pairs using 58 boxes) installed in our study area. Typical of tropical species, the average clutch was small (2.19 ± 0.55 [SD] over 431 nesting attempts), but pairs nested repeatedly throughout the year. Pairs showed high site fidelity, and nestboxes (n = 70) installed at least 34 m from forest edge were readily colonized with 77% occupied by the end of our study. Protected nestboxes in urbanized areas along with snake suppression may be useful strategies for expanding the population of Micronesian Starlings and consequently restoring seed dispersal in nearby forest on Guam.